Refractory septic shock (Part 1) - L. L. Plotkin (Вестник анестезиологии и реаниматологии)
Refractory septic shock develops in 6–7% of sepsis patients with short-term lethality rate of more than 50%. It is necessary to assess the effectiveness of intensive therapy methods used in this case.The objective of the review: to analyze publications on the intensive care of refractory septic shock.Results. 56 studies published in the period from January 1, 1990 to September 1, 2020 were analysed, they reflect the effectiveness of some methods used for management of refractory septic shock (treatment of the underlying disease, liquid bolus, the use of norepinephrine, adjuvant therapy, management of metabolic acidosis). The second part of this article will reflect the evaluation of the effectiveness of other approaches to the treatment of this complication.